Guidelines for DC preparation and flow cytometry analysis of mouse nonlymphoid tissues - Probst, Hans Christian; Stoitzner, Patrizia; Amon, Lukas; Backer, Ronald A.; Brand, Anna; Chen, Jianzhou; Clausen, Björn E.; Dieckmann, Sophie; Dudziak, Diana; Heger, Lukas; Hodapp, Katrin; Hornsteiner, Florian; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various nonlymphoid tissues. DC are sentinels of the immune system present in almost every mammalian organ. Since they represent a rare cell population, DC need to be extracted from organs with protocols that are specifically developed for each tissue. This article provides detailed protocols for the preparation of single-cell suspensions from various mouse nonlymphoid tissues, including skin, intestine, lung, kidney, mammary glands, oral mucosa and transplantable tumors. Furthermore, our guidelines include comprehensive protocols for multiplex flow cytometry analysis of DC subsets and feature top tricks for their proper discrimination from other myeloid cells. With this collection, we provide guidelines for in-depth analysis of DC subsets that will advance our understanding of their respective roles in healthy and diseased tissues. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all coauthors, making it an essential resource for basic and clinical DC immunologists.
Created from Fastlane, Scopus look-up
Keywords: Dendritic cells; Discrimination of dendritic cell subsets; Mouse nonlymphoid tissue; Multiplex flow cytometry analysis; Tissue digestion protocols